Gravity Imaging Radio Observer (GIRO) for Planetary Science and Mission Opportunities - R. S. Park; J. E. Riedel; E. J. Brandon; N. E. Harvey; S. Manafi; M. C. Smart; Z. J. Towfic; A. Berne; W. I. Bertiger; J. T. Keane; A. S. Konopliv; N. Mastrodemos; et al. (The Planetary Science Journal)
The Gravity Imaging Radio Observer (GIRO) is a concept for a high-performance, battery-powered radio probe designed to be released in the proximity of a target planetary body to study its gravitational variations. Using the host spacecraft’s communications system, the GIRO probes would receive and transmit a coherent carrier signal back to a host spacecraft, providing high-precision range-rate data with accuracy ≤1 μ m s ^−1 at a 60 s count time, which is 10–100 times better than the performance of conventional ground-based radiometric data. GIRO is spin stabilized, which significantly reduces nongravitational perturbations, making it ideal for acquiring clean gravitational signals for exploring planetary interiors. Additionally, the use of a specifically designed, carrier-only, analog transponder makes GIRO low cost. Furthermore, a host spacecraft could release multiple GIROs, reducing risk when exploring hazardous environments. In this paper, we describe the GIRO probe and deployer design concept and present scenarios where GIRO enables gravity measurements that would be challenging to achieve with conventional approaches.